Molecular landscape of CAPN3 mutations in limb-girdle muscular dystrophy type R1: from a Chinese multicentre analysis to a worldwide perspective. Issue 11 (29th September 2020) - Zhong, Huahua; Zheng, Yiming; Zhao, Zhe; Lin, Pengfei; Xi, Jianying; Zhu, Wenhua; Lin, Jie; Lu, Jun; Yu, Meng; Zhang, Wei; Lv, He; Yan, Chuanzhu; et al.
Abstract : Background: Limb-girdle muscular dystrophy type R1 (LGMDR1) can be caused by recessive CAPN3 mutations accounting for the majority of LGMD. To date, no systemic evaluation has been performed to analyse the detrimental and normal mutations on CAPN3 and its hotspots. Methods: CAPN3 variants (n=112) from a total of 124 patients with LGMDR1 recruited in four centres in China were retrospectively analysed. Then external CAPN3 variants (n=2031) from online databases were integrated with our Chinese cohort data to achieve a worldwide perspective on CAPN3 mutations. According to their related phenotypes (LGMDR1 or normal), we analysed consequence, distribution, ethnicity and severity scores of CAPN3 mutations. Results: Two hotspot mutations were identified including c.2120A>G in Chinese population and c.550del in Europe. According to the integrated dataset, 521 mutations were classified as LGMDR1-related and converged on exons 1, 10, 5, 22 and 13 of CAPN3. The remaining 1585 variants were classified as normal-population related. The deleterious ratio of LGMDR1-relevant variants to total variants in each population was 0.26 on average with a maximum of 0.35 in Finns and a minimum of 0.21 in South Asians. Severity evaluation showed that Chinese LGMDR1-related variants exhibited a higher risk (Combined Annotation Dependent Depletion score +1.10) than that from database patients (p<0.001). Conclusions: This study confirmed two hotspots and LGMDR1-related CAPN3 variants, highlighting the advantages in using a data-based comprehensive analysis to achieve a genetic landscape for patients with LGMDR1.